Harry Potter and the chamber of secrets - Rowling, J. K. (Bloomsbury London, 2014)
Harry Potter can't wait for his holidays with the dire Dursleys to end. But a small, self-punishing house-elf warns Harry of mortal danger awaiting him at Hogwarts. Returning to the castle nevertheless, Harry hears a rumour about a Chamber of Secrets, holding unknown horrors for wizards of Muggle parentage. Now someone is casting spells that turn people to stone, and a terrible warning is found painted on the wall. The chief suspect, always in the wrong place - is Harry. But something much more terrifying has yet to be unleashed